Community Trait Responses of Three Dominant Macrophytes to Variations in Flooding During 2011–2019 in a Yangtze River-Connected Floodplain Wetland (Dongting Lake, China) - Huang, Ying; Chen, Xin-Sheng; Li, Feng; Hou, Zhi-Yong; Li, Xu; Zeng, Jing; Deng, Zheng-Miao; Zou, Ye-Ai; Xie, Yong-Hong (Frontiers in Plant Science, 2021)
In lacustrine wetlands connected to rivers, the changes in flood regimes caused by hydrological projects lead to changes in the community traits of dominant macrophytes and, consequently, influence the structure and function of wetland vegetation. However, community trait responses of macrophytes to the timing and duration of flood disturbance have been rarely quantified. In 2011–2019, we investigated plant species diversity, density, and biomass in three dominant macrophyte communities (Carex brevicuspis C.B. Clarke, Miscanthus sacchariflorus (Maxim.) Hackel, and Polygonum hydropiper L.) through monthly field surveys in Dongting Lake wetlands. Partial least squares regressions were used to analyze how the variations in hydrological regimes affected plant community traits. Apparent inter-annual fluctuations in plant community traits were detected during 2011–2019. The species richness and Shannon index of diversity of Miscanthus and Polygonum communities increased, whereas the Shannon index of diversity of Carex community decreased. Variation in flooding had a greater effect on Polygonum and Carex community traits than on Miscanthus community traits. Flooding disturbed all plant communities, especially when the duration and timing varied. Shorter inundation periods caused the biomass of Miscanthus community to decline, and that of Carex and Polygonum communities to increase. Earlier flood recession caused the species richness and Shannon index of diversity of Polygonum and Miscanthus community to increase, and those of Carex community to decrease. These findings imply that shorter inundation durations and earlier flood recession generated by the operation of Three Gorges Dam has changed the macrophyte growth pattern.